The impact of purchasing strategy-structure (mis)fit on purchasing cost and innovation performance. Issue 1 (January 2018) - Akın Ateş, Melek; van Raaij, Erik M.; Wynstra, Finn
Abstract: The organizational design literature strongly supports the notion of "structure follows strategy", and suggests that a misfit between the two has a negative effect on performance. Building on this line of argument, we examine to what extent the (mis)fit between purchasing strategy and purchasing structure impacts purchasing performance. We focus on cost and innovation purchase category strategies, and examine how the deviation from an ideal purchasing structure defined along three dimensions (centralization, formalization, and cross-functionality) impacts purchasing performance. Analysing data collected from 469 firms in ten countries, we demonstrate that a strategy-structure misfit negatively impacts purchasing performance in both cost and innovation strategies. We also find that purchasing proficiency is a mediator in this relationship between misfit and performance. Our findings aid managerial decision making by empirically validating the necessity of having the right purchasing structure for successfully executing different purchasing strategies. Highlights: Purchasing strategy and purchasing structure vary across purchase categories. Purchasing strategy-structure misfit is negatively related to purchasing performance. Purchasing proficiency is a mediator between misfit and purchasing performance.